Forming limit curves in low-carbon steels: improved prediction by incorporating microstructural evolution. Issue 1 (September 2016) - Vadavadagi, B.; Shekhawat, S.; Samajdar, I.; Narasimhan, K.
Abstract Experimental forming limit curves (FLCs) were determined for two different grades of low-carbon steel: interstitial free (IF) and drawing quality (DQ). The grades had different interstitial content, clear differences in microstructural evolution, and differences in experimental FLCs. Microstructural evolution was generalized in terms of developments in crystallographic texture and in-grain misorientations. These were extrapolated further into dynamic values of normal anisotropy ( r ¯ $$ \overline{r} $$ ) and strain hardening exponent (n ), respectively. FLCs were simulated by finite element (FE) analysis. Simulations were conducted using constant (or initial) and dynamic material properties (namely, r ¯ $$ \overline{r} $$ andn ). Simulations using the dynamic variation in the material properties showed better comparison to the experimental FLCs.